Analysis of the fulfillment of decent living needs of indigenous Papuan traders at the Central Market of Timika, Central Papua - Noya, Appres; Marlissa, Elsyan R.; Urip, Transna Putra (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the extent to which Indigenous Papuan (OAP) traders at the Timika Central Market in Central Papua are able to meet the standards of a Decent Living Needs (Kebutuhan Hidup Feasible/KHL), particularly in relation to their income and family responsibilities. Research/methodology: A mixed-method approach was employed, combining quantitative data from 73 respondents via structured questionnaires and qualitative insights through in-depth interviews and direct observation. The analysis utilized descriptive statistics to assess income and expenditures, and benchmarked them against the standard living needs set by national regulations (Permenakertrans RI No. 13/2012). Results: The findings indicate that 87.67% of the OAP traders earned incomes sufficient to meet the KHL standards for their household size, while 12.33% were found to be below the KHL threshold due to high family dependency ratios. The most significant income sources came from selling local agricultural products, crafts (e.g., noken), and forest-based commodities. Challenges included limited access to capital, lack of managerial and digital literacy, and minimal government support. Conclusions: Most OAP traders at Timika Central Market meet the Decent Living Needs standard, but some remain vulnerable due to low income and high family burdens. Strengthening government support is essential to improve their welfare and business sustainability. Limitations: The study is geographically limited to one market in Central Papua and focuses only on OAP traders, which may not fully represent conditions in other informal trading centers across Papua or Indonesia. Contribution: This study provides empirical evidence of the socioeconomic struggles and resilience of Indigenous traders in the informal economy. It highlights the need for tailored policies and empowerment programs, and contributes to the literature on local economic development, informal labor markets, and indigenous livelihoods.